Batch Adsorption Of Bisphenol A (Bpa) On Coconut Shell Activated Carbon - Azlan, Nur Qistina Azfa Mohd (Universiti Sains Malaysia, 2022)
The problem of water contamination caused by emerging contaminant (EC) or in other words organic residue like Bisphenol A (BPA) residues found in natural wastewater streams has recently gotten a lot worse. This EC also being considered as one of the endocrine-disrupting compounds (EDC) that may threaten human health and usually found in the water bodies. In this study, series of experiments in batch adsorption of BPA of coconut shell activated carbon were conducted to investigate the adsorption properties of BPA at various parameters such as initial concentrations of BPA, temperatures as well as adsorbent dosage. The coconut shell activated carbon had a pore size range of 0.425 to 0.152 mm. The maximum adsorption capacity, Qm was 279.5864 mg/g at 50 ℃. Moreover, the pseudo-first-order kinetics model possessed a better fit to the experimental data. In terms of thermodynamic, the BPA adsorption on the coconut shell activated carbon was identified as spontaneous and exothermic process in nature. As for the adsorption profile of BPA was the best fitted in the Langmuir isotherms model, suggesting that monolayer adsorption on the active sites of the adsorbent while experiencing the homogenous surface on the adsorbent’s surface. Therefore, according to the isotherm, kinetic and thermodynamic results, we could summarize that the BPA adsorption of coconut shell activated carbon following the physisorption mechanism.